2017
DOI: 10.1097/pai.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Reduced E-Cadherin and Aberrant β-Catenin Expression are Associated With Advanced Disease in Signet-Ring Cell Carcinomas

Abstract: Signet-ring cell carcinomas (SRCCs) tend to present at higher stages and thus are generally associated with a worse prognosis. It has been postulated that a deficiency of E-cadherin may be causal in the pathogenesis of SRCC in animal models. In this study, we systemically analyzed the expression of E-cadherin and β-catenin, a key component of the cadherin complex, in 137 consecutive SRCCs of various organ systems to explore the significance of these molecules in the pathogenesis and progression of SRCCs. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This phenomenon was exclusively seen in the signet ring cells but not non-signet ring cells, thus recapitulating our previous observations (table 1 and figure 1A–F) 15. Interestingly, this reduction was less frequently seen in the signet ring cells of the metastatic deposits when compared with their primary counterparts, and was only found in cells of 21 tumours (57%) in the lymph node metastasis or at distant sites of relapse (table 1 and figure 1G–L) (OR 0.36; χ 2 =3.95, 95% CI 0.13 to 1.0; p=0.047).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This phenomenon was exclusively seen in the signet ring cells but not non-signet ring cells, thus recapitulating our previous observations (table 1 and figure 1A–F) 15. Interestingly, this reduction was less frequently seen in the signet ring cells of the metastatic deposits when compared with their primary counterparts, and was only found in cells of 21 tumours (57%) in the lymph node metastasis or at distant sites of relapse (table 1 and figure 1G–L) (OR 0.36; χ 2 =3.95, 95% CI 0.13 to 1.0; p=0.047).…”
Section: Resultssupporting
confidence: 92%
“…We previously found that loss of E-cadherin was a frequent event in SRCC of various organs, and this reduction was more prominent in signet ring cells than that in non-signet ring cells of the same tumours 15. In this study, we extended these observations and found that overall E-cadherin expression was significantly higher in the metastatic deposits of SRCC than in the primary sites, thus supporting the potential role of E-cadherin in the process of MET as speculated previously.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Signet-ring cells are thought to derive from cellular alterations including abrogation of cell-to-cell adhesion, enhancement of mucin production, and disruption of mucin secretion. These mechanisms are thought to contribute to signet-ring morphology in carcinomas regardless of primary site [12, 13, 14]. While their morphology may be similar from organ-to-organ, they typically retain expression of markers from their site of origin [15].…”
Section: Discussionmentioning
confidence: 99%